Evaluating Bahasa Inggris Work in Progress: A Comprehensive Analysis of Indonesia’s Merdeka Curriculum English Textbook for Grade X Using Cunningsworth and Al-Sowat Framework - Muzri. S, Ahsan; Dollah, Syarifuddin; Sunra, La; Rawikarani, Dias Wahyu (JELITA, 2025)
This study aims to evaluate the quality of the English textbook Bahasa Inggris Work in Progress for grade X used in the implementation Merdeka Curriculum in Indonesia. This book was evaluated using a descriptive quantitative approach with an instrument based on the Cunningsworth (1995) and Al-Sowat (2012) evaluation framework, which covers nine main aspects: layout, content, objectives, language types, language skills, activities, structure and vocabulary, cultural values, and teacher needs. The evaluation results indicate that this book has quite good quality in terms of layout, content, and teacher support, and covers all four language skills in a balanced manner. However, several weaknesses were found, including the lack of integration of cultural values, the suboptimal development of critical thinking and problem-solving skills, and the limited authentic activities that reflect real life. This book also does not fully consider differences in student learning styles and does not provide a means for independent reflection on learning. Therefore, improvements are needed in the development of cultural content, the variety of high-level activities, and the preparation of formative assessments. The results of this study contribute to curriculum developers, textbook writers, and educators in improving the effectiveness of teaching materials that align with the principles of differentiated learning and strengthening 21st century competencies in Merdeka Curriculum.